2008
DOI: 10.1002/hup.934
|View full text |Cite
|
Sign up to set email alerts
|

Diminished 5‐HT functioning in CBCL pediatric bipolar disorder‐profiled ADHD patients versus normal ADHD: susceptibility to rapid tryptophan depletion influences reaction time performance

Abstract: The results suggest alterations in 5-HT functioning in CBCL-PBD-spectrum patients, and 'aggression' as a potential moderator variable to ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 38 publications
(44 reference statements)
0
46
0
Order By: Relevance
“…The diagnostic value of the CBCL-DP has been discussed in recent years. Previous studies have revealed evidence of high heritability [4,7,8], longitudinal stability [8], stability across ages [4,5,9] and neurobiological basis [10,11]. In addition, there is a growing consensus that the CBCL-DP phenotype should be considered an indicator of poor self-regulation, overall psychopathology, symptom severity, exposure to psychosocial adversity and functional impairment [12,13,14,15,16,17], as well as a heritable trait that increases susceptibility for later psychopathology and impairment [5,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic value of the CBCL-DP has been discussed in recent years. Previous studies have revealed evidence of high heritability [4,7,8], longitudinal stability [8], stability across ages [4,5,9] and neurobiological basis [10,11]. In addition, there is a growing consensus that the CBCL-DP phenotype should be considered an indicator of poor self-regulation, overall psychopathology, symptom severity, exposure to psychosocial adversity and functional impairment [12,13,14,15,16,17], as well as a heritable trait that increases susceptibility for later psychopathology and impairment [5,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have examined the neurobiology underlying the behavioral phenotype captured by the CBCL-DP and presented evidence of genetic [7,11,16] , neurometabolic [17] and endocrinologic [18] characteristics of CBCL-DP.…”
mentioning
confidence: 99%
“…First and foremost, apart from the double-blind within-subject repeated measures design it included a healthy control group that did not differ from the patients in education, IQ or age, which was not possible in previous research [34], [39], [40], [41]. Second, using the same behavioral paradigm as previous research with children and adolescents allows us to look at the behavioral data from a developmental viewpoint as part of an iterative approach that focuses on the neurobiological underpinnings of anger reactive aggression in ADHD.…”
Section: Discussionmentioning
confidence: 99%